2001
DOI: 10.1002/1521-4095(200109)13:18<1377::aid-adma1377>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Mesoporous Thin TiO2 Films with Hexagonal Pore Structures Using Triblock Copolymer Templates

Abstract: TiO2 thin films with a hexagonal mesoporous structure and an anatase‐type crystalline framework are easily synthesized by a sol–gel method at low pH, using an EO–PO–EO block copolymer as template. While the TiO2/polymer superstructure originally has a primitive cubic structure, annealing at 150 °C affords a phase transition to hexagonal (see Figure), which persists upon template removal by calcination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
125
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(129 citation statements)
references
References 1 publication
3
125
0
1
Order By: Relevance
“…Серед них можна виділити: золь-гель метод [21][22][23], метод осадження з безводного рідинного середовища [24][25][26], гідротермальний [27][28][29], темплатний [30][31][32], сольвотермальний [33][34][35] методи, метод анодного окиснення [36], міцелярний метод [37][38], хімічне осадження з парової фази [39], сонохімічний [40][41][42], та мікрохвильовий [43][44][45] методи. Проте, саме гідро-термальна обробка відкриває широкі можливості для керування морфологією TiO 2 та розміром і ступенем кристалічності його частинок [46].…”
Section: вступunclassified
“…Серед них можна виділити: золь-гель метод [21][22][23], метод осадження з безводного рідинного середовища [24][25][26], гідротермальний [27][28][29], темплатний [30][31][32], сольвотермальний [33][34][35] методи, метод анодного окиснення [36], міцелярний метод [37][38], хімічне осадження з парової фази [39], сонохімічний [40][41][42], та мікрохвильовий [43][44][45] методи. Проте, саме гідро-термальна обробка відкриває широкі можливості для керування морфологією TiO 2 та розміром і ступенем кристалічності його частинок [46].…”
Section: вступunclassified
“…The most convenient method of preparing mesoporous titania films is solvent evaporation, which was first proposed by Ogawa [18,19]. Through the coating of precursor solutions, which include ethanol, inorganic species and surfactants, mesoporous titania films with various mesostructures, such as lamellar and 2D hexagonal mesostructures, can be prepared [20][21][22][23][24]. Yun et al reported the first example of anatase-crystallized mesoporous titania thin films with a 2D hexagonal mesoporous structure using the solvent evaporation method (figure 2(a)) [20].…”
Section: Mesoporous Titania Filmsmentioning
confidence: 99%
“…Through the coating of precursor solutions, which include ethanol, inorganic species and surfactants, mesoporous titania films with various mesostructures, such as lamellar and 2D hexagonal mesostructures, can be prepared [20][21][22][23][24]. Yun et al reported the first example of anatase-crystallized mesoporous titania thin films with a 2D hexagonal mesoporous structure using the solvent evaporation method (figure 2(a)) [20]. Smarsly et al also applied the solvent evaporation method to fabricate highly organized mesoporous anatase films by the hydrolysis/condensation of TiCl 4 in the presence of polyhydroxybutyrate-(polyethylene oxide) block copolymer templates [22].…”
Section: Mesoporous Titania Filmsmentioning
confidence: 99%
“…It is not general although several methods have been applied into controlling the hydrolysis of inorganic precursors, for example, relying on metal chlorides and coordination (50,54). Templates removal is also very difficult since the unstable frameworks collapse during calcination owing to the crystallization of metal oxides at relative low temperatures (57,58). A better understanding of the interactions between precursors themselves is, therefore, beneficial for careful regulation of synthesis.…”
Section: Surfactant Self-assembly Approachmentioning
confidence: 99%